Survey of Schools: ICT in Education - European Schoolnet; University of Liege Psychology and Education (Publications Office of the European Union, 2013)
Based on over 190,000 responses from students, teachers and head teachers collected and analysed during the school year 2011-12, the Survey of Schools: ICT in Education provides detailed, up-to-date and reliable benchmarking of Information and Communication Technologies in school level educationacross Europe, painting a picture of educational technology in schools: from infrastructure provision to use, confidence and attitudes. The Survey was commissioned in 2011 by the European Commission (Directorate General Communications Networks, Content and Technology) to benchmark access, use and attitudes to ICT in schools in 31 countries (EU27, Croatia, Iceland, Norway and Turkey). The Survey is one of a series within the European Union’s cross-sector benchmarking activities comparing national progress towards the Digital Agenda for Europe (DAE) and EU2020 goals. The Survey was conducted in partnership between European Schoolnet and the University of Liège (Service d’Approches Quantitatives des faits éducatifs, Department of Education). It is the first Europe-wide exercise of this type for six years, following the eEurope 2002 and eEurope 2005 surveys. It is the first to be conducted online and the first to include students directly. Work on the survey took place between January 2011 and November 2012, with data collection in autumn 2011. The survey report and all related materials are freely available on the European Commission’s Digital Agenda Scoreboard website1. In four countries (Germany, Iceland, Netherlands and the United Kingdom) the response rate was insufficient, making reliable analysis of the data impossible; therefore the findings in this report are based on data from 27 countries. http://ec.europa.eu/digital-agenda/en/news/survey-schools-ict-education